Correlation between the Severity and Type of Acne Lesions with Serum Zinc Levels in Patients with Acne Vulgaris - Rostami Mogaddam, Majid (Hindawi Publishing Corporation, 2014)
Acne vulgaris is the most common cutaneous disorder affecting adolescents and young adults. Some studies have reported an association between serum zinc levels and acne vulgaris. We aimed to evaluate the serum zinc level in patients with acne vulgaris and compare it with healthy controls. One hundred patients with acne vulgaris and 100 healthy controls were referred to our clinic. Acne severity was classified according to Global Acne Grading System (GAGS). Atomic absorption spectrophotometry was used to measure serum zinc levels. Mean serum level of zinc in acne patients and controls was 81.31 ± 17.63 μg/dl and 82.63 ± 17.49 μg/dl, respectively. Although the mean serum zinc level was lower in acne group, it was not statistically significant (P = 0.598). There was a correlation between serum zinc levels with severity and type of acne lesions. The results of our study suggest that zinc levels may be related to the severity and type of acne lesions in patients with acne vulgaris. Relative decrease of serum zinc level in acne patients suggests a role for zinc in the pathogenesis of acne vulgaris.